Modelling the benefits of urine source separation scenarios on wastewater treatment plants within an urban water basin. (11th July 2022) - Matar, Gerald; Besson, Mathilde; Mas, Jennifer; Azimi, Sam; Rocher, Vincent; Sperandio, Mathieu
Abstract: Stringent discharge regulations are encouraging researchers to create innovative and sustainable wastewater treatment solutions. Urine source separation (USS) is among the potent approaches that may reduce nutrient peak loads in the influent wastewater and improve nutrient recovery. A phenomenological model was used to simulate dynamic influent properties and predict the advantages gained from implementing USS in an urban water basin. Several scenarios were investigated assuming different levels of deployment: at the entire city, or specifically in office buildings for men's urine only, or for both men and women employees. The results confirmed that all scenarios of urine source separation offered benefits at the treatment plant in terms of reducing nitrogen influent load. The economic benefits in terms of reducing energy consumption for nitrification and decreasing methanol addition for denitrification were quantified, and results confirmed environmental advantages gained from different USS scenarios. Despite larger advantages gained from a global USS rate in an entire city, implementation of a specific USS in office buildings would remain more feasible from a logistical perspective. A significant benefit in terms of reducing greenhouse gas emissions is demonstrated and this was especially due to the high level of N2 O emissions avoided in nitrifying biological aerated filter. HIGHLIGHTS: A methodology for modelling different urine separation scenarios in an urban area is shown. An influent generator was calibrated and gives the variation of effluent quality. Savings in aeration and methanol are quantified at the treatment plant. Important reduction of greenhouse gas emissions is shown for different recovery techniques. The benefits are related to the reduction in N2 O emissions and N fertilizer substitution.